Analysis of person-situation interactions in educational settings via cross-classified multilevel longitudinal modeling: illustrated with the example of students’ stress experience - Kärner, Tobias; Sembill, Detlef; Aßmann, Christian; Friederichs, Edgar; Carstensen, Claus H. (Frontline Learning Research, 2017)
The investigation of learning processes by assessing students’ experience along with objective characteristics within a classroom context has a long tradition in empirical learning process research (e.g. Sembill, 1984 et passim; Wild & Krapp, 1996). However, most of the existing studies confine themselves to psychological variables that seem to be too narrowly considered, as there is theoretical and empirical evidence proving the involvement of somatic and psychological processes in learning and in stress reactions. Furthermore there is a lack of studies that investigate situation-related experience (states) as an outcome of interactions between relatively stable characteristics (traits) and continuously changing “objective” context conditions. Against this background, we will present an approach for cross-classified multilevel longitudinal modelling of person-situation interactions in naturalistic educational settings. We illustrated our model with the example of students’ stress experience referring to empirical data that we measured within a multidisciplinary research project (pedagogy, psychology, adolescent medicine). 53 students at a public German vocational school were investigated during 9 lessons. There are up to 38 state measurements per person, resulting in 2,014 measurements in total. Taking into account that states are nested within persons and within situations we applied a cross-classified multilevel model to analyse effects on students’ stress experience. The analysis shows significant person-situation interactions between academic self-concept and classroom demands and between baseline cortisol concentration and classroom demands: the relation between classroom demands and stress experience depends on relatively stable person-related characteristics. A deeper knowledge about the complex interrelations between traits, states, and continuously changing context conditions seems to be essential for a more holistic understanding of learning at school and for the identification of crucial aspects for an evidence-based design and implementation of teaching and learning arrangements.